Association between thyroid cancer and epidermal growth factor receptor mutation in female with nonsmall cell lung cancer - Kim, Seo Yun (Ann Thorac Med, 2017)
BACKGROUND: The aim of this study was to investigate the association between epidermal growth factor receptor (EGFR) mutation and thyroid cancer in female patients with nonsmall-cell lung cancer (NSCLC). METHODS: In a retrospective study, we examined 835 female patients who were diagnosed with NSCLC and underwent an EGFR mutation test between June 2003 and August 2013. The associations of EGFR mutation with thyroid cancer and a family history of thyroid cancer were evaluated using logistic regression models. RESULTS: EGFR mutation was found in 378 of 835 patients. In addition to adenocarcinoma (P < 0.001), EGFR mutations were positively associated with a personal history of thyroid cancer (5.8% versus 2.6%; P = 0.020), while showing a trend toward inverse association with a personal history of nonthyroid cancer (5.8% vs. 9.0%; P = 0.086). Likewise, the incidence of EGFR mutations was associated with a family history of thyroid cancer (2.9% vs. 0.9%; P = 0.028), while showing a trend toward inverse association with a family history of nonthyroid cancer (27.8% vs. 33.7%; P = 0.066). Multivariate logistic regression showed that the incidence of EGFR mutations was different in women with thyroid or nonthyroid cancer (P = 0.035) and in women with a family history of thyroid or nonthyroid cancer (P = 0.023). CONCLUSIONS: Our data suggest that thyroid cancer and a family history of thyroid cancer are associated with EGFR-mutated NSCLC in female patients. The differences in the incidence of thyroid cancer and a family history of thyroid cancer by EGFR mutational status provide new insight into pathogenesis of this genetic change.